(untitled) (Baghdad Science Journal, 2017)
The chamomile is one of the most important medicinal plants recommended for treatment of asthma and some respiratory system diseases. This research was designed to research the effects of aqueous extract of chamomillarecutita on histological structure of Diaphragm of albino mice. The study included 40 male albino mice Musmusculus, their age ranged from (5-7) weeks.The mices were divided randomly to 5 groups and oral administered with 1 ml every day for 10 days:- First Group G1: consider as control group and treated with normal saline,Second Group G2: was treated with aqueous extract of chamomile with concentration of 3 gm /100 ml D.W, Third Group G3: was treated with aqueous extract of chamomile with concentration of 5 gm /100 ml D.W.Fourth Group G4: was treated with aqueous extract of chamomile with concentration of 7 gm /100 ml D.W and the Fifth Group G5: was treated with aqueous extract of chamomile with concentration of 10 gm /100 ml D.W. Theresults of microscopic examination of diaphragm sections of groups G3,G4 and G5 showed degenerative effects on muscular tissue in way of breaking of myofibrils differences in their sizes and degeneration of most of nuclei of muscle fiber and their migration to inside the muscle fiber , it has been found that these treatments cause an alteration in myofibril in fibrotic myofibril. From this study we conclude that low concentration of aqueous extract of chamomile have low side effect on major respiratory muscles and could be used in beneficial treatment to contact diseases of respiratory system but without longer duration.